Lymphadenectomy in endometrial cancer – achieving more with less?. Issue 4 (1st April 2022) - Gitas, Georgios; Freytag, Damaris; Allahqoli, Leila; Baum, Sascha; Rody, Achim; Maass, Nicolai; Dinas, Konstantinos; Laganà, Antonio Simone; Moawad, Gaby; Sotiriadis, Alexandros; Alkatout, Ibrahim
Abstract: The lymph node status of patients with endometrial cancer is known to be a crucial determinant for the prognosis of the disease. It also provides the indication for further adjuvant treatment. The staging of endometrial cancer by surgery has been a controversial issue for more than 30 years. The significant complication rate after lymphadenectomy and the development of minimally invasive surgery have led to the use of sentinel lymph node (SLN) mapping. In the present review, we present the development of surgical staging procedures in patients with endometrial cancer and summarize the recently expanding body of published literature on the subject. SLN mapping is a safe and accurate technique, especially when indocyanine green is used as a tracer. SLN mapping appears to reduce complication rates as well as costs without affecting the oncologic outcome. Large prospective studies are needed to establish the effects of SLN mapping on the outcome of disease, especially in high-risk patients with endometrial cancer. Furthermore, the need for additional systematic lymphadenectomy prior to adjuvant radio-chemotherapy in patients diagnosed with isolated lymph node metastasis during SLN biopsy must be investigated further. This might pave the way for a new surgical approach in patients with endometrial cancer.